Squid daddy's delivery room in the seas of Taiwan - Public Television Service ([Taiwan] : Public Television Service, 2007)
A volunteer marine conservation team led by Kuo Tao-jen has built the first-ever'bamboo-groove condominium-cum-delivery room' for spawning oval squids along the northeastern coast of Taiwan-an undertaking that integrates the work of restoration, research and education with tourism and creation of economic value
DVD format
Subtitles in Traditional Chinese, English, Francais and Espanol
Keywords: Squids -- Taiwan